The Influence of Mix Freeze Group Strategy and Motivation Toward English Foreign Language Students' Reading Comprehension Ability - Musdizal Azis; Suhaimi Suhaimi (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2024)
This research was aimed at knowing the students' reading comprehension ability who were taught through mix freeze group strategy and conventional teaching; the reading comprehension of high motivated students who were taught through mix freeze group strategy and conventional teaching; the reading comprehension of low motivated students who were taught through mix freeze group strategy and conventional teaching; the interaction between both model of teaching and motivation toward students' reading comprehensioan ability. This reserch was a quasi-experimental research by factorial 2x2 design. The data were collected by using test and questionnaire. Based on the research findings and data analysis, it can be concluded that: 1). Students' reading comprehension ability who are taught through mix freeze groups strategy are better than those of conventional teaching. 2). High motivated students' reading comprehension ability who are taught through mix freeze groups strategy are better than those of conventional teaching. 3). Low motivated students' reading comprehension ability who are taught through mix freeze groups strategy are better than those of conventional teaching. 4) There is no interaction between mix freeze groups strategy and conventional teaching and motivation toward students' reading comprehension ability. It means that mix freeze groups strategy and conventional teaching can be used without considering students' pre-requisite motivation. The data shows that mix freeze groups strategy is more effective than conventional teaching. It could be concluded that students' reading comprehension ability is not affected by motivation but mix freeze groups strategy.